Poznański Czerwiec 1956-1986 [blok znaczków podziemnych] . Poznań's June 1956-1986. Sheet of unofficial stamps - Poczta Solidarność. (Poczta Solidarność, 1986)
Brown print on white paper, with perforation. Sheet, with "Poczta Solidarność" imprint, issued on the 30th anniversary of the June 1956 street protests in Poznań, consists of 4 stamps which represent posters related to the event. Price range: 15-70 zł per stamp.